Immunoglobulin levels in infantile pneumocystosis. Issue 2 (February 1972) - Kohout, Elfriede; Post, Cornelius; Azadeh, Bahram; Dutz, Werner; Bandarizadeh, Bashi; Kadivar, Darius
Abstract : Two hundred and twelve determinations of IgA, IgG, and IgM were performed in 50 infants during an epidemic of interstitial plasma cell pneumonia. Criteria for diagnosis are discussed. The immunoglobulin levels in pneumocystic, non-pneumocystic, and normal American infants are compared. An analysis of the findings in individual cases reveals a time-related immunoglobulin response, which helps to elucidate the pathogenicity of the disease.